Keberadaan Ekonomi Islam dan Praktik Ekonomi Islam Pada Masa Rasulullah SAW - Rossidah Rihadatul Aisi; Rina Tri Astuti; Anggi Permatasari; Triana Dani Maulana; Muhammad Taufiq Abadi; Muhammad Aris Syafi’i (JURNAL ILMIAH RESEARCH STUDENT, 2024)
The purpose of this paper is to study the habits and methods of Islamic Economic during the time of The Prophet. Islamic principles from the Al- Quran dan Hadits serve as Islamic Economic . To Realize civil society, Islamic economic is practiced . the economic system has been changed so that so that everyone can benefit from it as a result of the prophet muhammad who was a role model for everyone in various aspects of life . the prophet muhammad was the leader and prophet of allah in the pre-islam peroid . he also modified the country economic and financial structure in accordance with the teachings of the koran and sunnah of the prophet muhammad . in addition ,the prophet muhammad was the firts pioneer in implementing islamic economic policies.